Evaluation of anti-IL-6 monoclonal antibody therapy using murine type II collagen-induced arthritis - Shealy David; Gardner Debra; Wu Bin; Song Zheng; Liang Bailin; Song Xiao-Yu; Wooley Paul H (BMC, 2009)
Abstract Interleukin-6 is a multifunctional cytokine that is critical for T/B-cell differentiation and maturation, immunoglobulin secretion, acute-phase protein production, and macrophage/monocyte functions. Extensive research into the biology of IL-6 has implicated IL-6 in the pathophysiology and pathogenesis of RA. An anti-murine IL-6 mAb that neutralizes mouse IL-6 activities was tested in animal model of collagen-induced arthritis. Prophylactic treatment with anti-IL-6 mAb significantly reduced the incidence and severity of arthritis compared to control mAb treated mice. The mitogenic response of B and T cells isolated from the lymph nodes of anti-IL-6 treated mice was significantly reduced compared to cells isolated from control mAb treated mice. The overall histopathology score for paws from the anti-IL-6 treated mice was significantly reduced when compared to paws from mice treated with control mAb, including both inflammatory (synovitis and pannus) and erosive (erosions and architecture) parameters. Reduced loss of cartilage matrix components was also observed in the anti-IL-6 treated mice. Collectively, these data suggest that IL-6 plays a major role in the pathophysiology of rheumatoid arthritis, and thus support the potential benefit of anti-IL-6 mAb treatment in rheumatoid arthritis patients.